THU0114 MITIGATING MEDICATION RISK AVERSION IN THE CONFIDENT TREATMENT DECISIONS FOR LIVING WITH RHEUMATOID ARTHRITIS TRIAL. (June 2019) - Danila, Maria; Chen, Lang; Owensby, Justin; O'beirne, Ronan; Melnick, Josh; Ruderman, Eric; Harrold, Leslie; Curtis, Jeffrey
Abstract : Background: Controlling disease activity in RA using a treat-to-target (T2T) strategy can optimize clinical and patient-important outcomes. Yet, many patients are not familiar with T2T and report medication risk aversion as a major barrier to changing therapy. Objectives: To develop and evaluate an educational, direct-to-patient video intervention aimed at improving willingness of patients to appropriately escalate treatment in RA. Methods: We conducted a controlled, randomized trial of our intervention among US patients with self-reported RA enrolled in the ArthritisPower patient registry. We recruited participants by email, and surveyed their satisfaction with disease control, values about RA medications, decisional conflict and willingness to change treatment if/when recommended by their rheumatologist. Intervention group participants were invited to view up to 6 videos (3 required) relevant to T2T; those in the control group viewed 2 vaccination-related videos unrelated to T2T as an "attention control". The primary outcome, collected using surveys, was patient-reported willingness to change RA treatment, measured by the choice predisposition scale (0-10, anchors: "Not willing at all"; "Extremely willing") that reflected preference for RA treatment change. We compared the difference in pre-post differences in willingness to change RA treatment between the two groups using t-test. Results: We invited 1264 RA patients by email. We reached our enrollment goal in 8 weeks. Study participants (N=208) were 90% Caucasian, 90% women, with mean (SD) age 50 (11) years, in good health (51%); 52% reported familiarity with T2T. A majority (89%) reported having values that favored RA medications. We observed no differences in baseline sociodemographics, patient global assessment of disease activity, health literacy, willingness to change treatment, or decisional conflict. We found a significant improvement in pre-post willingness to change treatment in intervention vs. control participants (0.5 vs 0.01, p=0.01). We calculated an effect size (Glass's delta) for the intervention of 0.48 (i.e. moderate). Moreover, decisional conflict about treatment change decreased; there was no significant difference in pre-post differences in decision conflict between groups. Conclusion: This randomized trial testing a novel patient-directed intervention advocating for T2T strategy implementation in RA care increased self-reported willingness to change RA treatment. Further studies are needed to evaluate if this effect is sustained over time and if it translates into actionable behavior change. Disclosure of Interests: Maria Danila Grant/research support from: Pfizer, Inc., Consultant for: Sanofi Genzyme & Regeneron, Lang Chen: None declared, Justin Owensby: None declared, Ronan O'Beirne Grant/research support from: Pfizer, Inc., Josh Melnick: None declared, Eric Ruderman Consultant for: Pfizer Inc., Leslie Harrold Shareholder of: Corrona, Grant/research support from: Pfizer, Consultant for: AbbVie, BMS, and Genentech, Employee of: Corrona, Jeffrey Curtis: None declared